The Spanish Civil War, the Soviet Union, and communism - Payne, Stanley G. (Yale University Press, 2004)
In this compelling text Stanley Payne offers a comprehensive narrative of Soviet and Communist intervention in the revolution and Civil War in Spain. He documents Soviet strategies Comintern activities and the role of the Communist party in Spain from the early 1930s to the end of the Civil War in 1939.